A novel method of diameter measurement of pistons used in pressure standards using scanning principle and fusion technique. (5th July 2018) - Sanjid, Mahammad Arif; Chaudhary, K P; Yadav, Sanjay; Sen, Mrinal; Ghoshal, Sanjoy K
Abstract: The requirement of improved certainties in the measurement of the diameter and the form of cylindrical artifacts is increasing day-by-day. Such requirements become indispensable in typical applications, like the inspection of the fuel injection systems and calibration of pressure balances. A new experiment is set to measure the diameter of a cylindrical artifact, particularly the piston of a pressure-measuring device. Three displacement sensors are used to scan the cross-section of a cylinder and a reference gauge block. At the same time, the scanning process is simulated for ideal conditions. The coordinate data thus obtained in the scanning is fused on to a circle. The misalignments in the experimental setup are refined by iterative scanning the artifacts under test until the experimentally obtained surface profiles match with the simulated ones. Then, the fused circle represents the diameter of the cylindrical object. According to substitution technique, the deviation of the diameter of the artifact under test is determined from the size of the gauge block. Finally, the expanded measurement uncertainty is estimated.